Whipping for adultery in the perspective of human rights in Lhokseumawe - Hamdani Hamdani; Muhammad Nasir; Ferdy Saputra; Putri Riana Sari (Geuthèë Institute, Aceh, 2023)
This study aims to evaluate the human rights implications of the whipping punishment for adultery cases in Lhokseumawe City, Indonesia. The research methods used in this research are empirical. Data was collected through a combination of fieldwork and libraries. The data were analyzed in a qualitative manner. The result of the study shows that the administration of the whipping punishment for adultery offenders does not violate human rights because it has been founded on Islamic law, specifically the Qur'an and Hadith in Aceh, and has taken into account the safety of whipping convicts. The whipping is considered a violation of human rights if used on innocent individuals. Whipping punishment is carried out in Aceh against convicts after obtaining approval from the Syari'ah Court, and the whipping punishment is conducted based on a court decision ordered with permanent legal effect. It is recommended that the Lhokseumawe Municipality Institution and the authorities strengthen and strictly enforce whipping restrictions so that whipping is produced in accordance with the principles of Islamic Shari'ah. Residents of Lhokseumawe should be more supportive and comply with the established regulations.